Role of LaNiO3 in suppressing voltage decay of layered lithium-rich cathode materials. (10th January 2018) - Wu, Feng; Li, Qing; Bao, Liying; Zheng, Yu; Lu, Yun; Su, Yuefeng; Wang, Jing; Chen, Shi; Chen, Renjie; Tian, Jun
Abstract: Lithium-rich cathode materials possess poor cycle stability and severe voltage decay during cycling. The main reason is that they suffer severe structure transformation during (I) Li2 MnO3 activation in the initial charge process accompanied with the release of O2 and the extraction of Li-ions from transition metal (TM) layer; (II) the migration of TM-ions (Mn 4+, Ni 2+ ) from TM layer to Li layer during cycling. Both of them accelerate phase transformation from the layered to LiNi x Mn2− x O4 (0 ≤ x ≤ 2) spinel structure. In order to solve this problem, LaNiO3 surface reorganization layer is proposed in this work. In the process of surface modification, the La salts are decomposed and then bond with Ni ions that diffused from the bulk of particles to the surface at high-temperature calcinations. Due to the strong LaO bond energy, there is less Li2 O removed and less lithium vacancy formed in TM layer during every charge processes. In addition, the stable existing form of Ni 3+ in material surface inhibits the migration of TM-ions from TM layer into Li layer. LaNiO3 surface can protect the electrode from the erosion by electrolyte, and effectively impede the electrode/electrolyte interface side reactions. Owing to the positive effects of LaNiO3 surface reorganization layer, the modified Li1.2 Mn0.6 Ni0.2 O2 samples exhibit superior high capacity retention (more than 87.7% after 200 cycles) with a significantly decrease in voltage decay, which exhibit an improvement over the state of art. Highlights: The strong LaO bond retards the Li2 O release and decreases Li-ion vacancy formed in TM layer during every charge processes. Ni 3+ stably exist in LaNiO3 surface reorganization layer, inhibiting the migration of Ni-ions from TM slabs to Li slabs. The LaNiO3 layer limits the transformation of the layered structure to spinel-like phase in Li-rich cathode material. The LaNiO3 layer suppresses voltage decay and improves electrochemical performance of Li1.2 Mn0.6 Ni0.2 O2 .